Effect of Hyperoxia on Retinoid Metabolism and Retinoid Receptor Expression in the Lungs of Newborn Mice - Chen, Hsing-Jin; Chiang, Bor-Luen (PLOS ONE, 2015)
Background Preterm newborns that receive oxygen therapy often develop bronchopulmonary dysplasia (BPD), which is abnormal lung development characterized by impaired alveologenesis. Oxygen-mediated injury is thought to disrupt normal lung growth and development. However, the mechanism of hyperoxia-induced BPD has not been extensively investigated. We established a neonatal mouse model to investigate the effects of normobaric hyperoxia on retinoid metabolism and retinoid receptor expression. Methods Newborn mice were exposed to hyperoxic or normoxic conditions for 15 days. The concentration of retinol and retinyl palmitate in the lung was measured by HPLC to gauge retinoid metabolism. Retinoid receptor mRNA levels were assessed by real-time PCR. Proliferation and retinoid receptor expression in A549 cells were assessed in the presence and absence of exogenous vitamin A. Results Hyperoxia significantly reduced the body and lung weight of neonatal mice. Hyperoxia also downregulated expression of RARα, RARγ, and RXRγ in the lungs of neonatal mice. In vitro, hyperoxia inhibited proliferation and expression of retinoid receptors in A549 cells. Conclusion Hyperoxia disrupted retinoid receptor expression in neonatal mice.